ANALISIS YURIDIS TERHADAP AKTA NOTARIS YANG DINYATAKAN TIDAK BERKEKUATAN HUKUM (Study Putusan Hakim No: 28/Pdt.G/2013/PN.Bdw) - Indriawati, Novia; Heriyanto, Heriyanto; Hofi, Moh. Ali (HUKMY : Jurnal Hukum, 2023)
Indonesian country as a country of law, in form of certainty of order legal protection notarial deeds made before a notary for all matters relating to agreements and will be stated in a notarial deed and the aim is to declare the deed inauthentic and will not be left to the judge to decide that the authentic deed is relegated to a deed under the hand and can be canceled and declared to be invalid or null and void by the deed. This research aims to understand the legal consequences of notarial deeds based on decisions (study decision number 28/Pdt.G/2017/PN Bdw). The legal position of parties who are declared to have no legal force, this research uses a normative juridical method and the approach used is a statutory, conseptual (doctrine) and case approach. The sources of legal materials used are primary legal materials, secondary legal materials, and tertary legal materials. And in this research, we use liblary data collection techniques (liberary research) and analyze the data deductively namely drawing conclusions from a general problem regarding the concrete problem being faced. The results found are contained in the decision of the panel of judges in Case Number 28/Pdt.G/2017/PN Bdw. In the considerations that the judge applied, it was in accordance with article 1865 of the Civil Code which states that every person who has claimed to have rights.